MODELLING OF NUCLEAR FUEL CLADDING TUBES CORROSION - Miroslav Cech; Martin Sevecek (Acta Polytechnica CTU Proceedings)
This paper describes materials made of zirconium-based alloys used for nuclear fuel cladding fabrication. It is focused on corrosion problems their theoretical description and modeling in nuclear engineering.